Proper, Weighty and Extremely Weighty Cause to End an Employment Contract in Finland - Mäkeläinen, Emma-Lotta; Toivonen, Sofia; Räsänen, Tiina (Udayana Journal of Law and Culture; Vol 2 No 1 (2018): Maintreaming Socio - Cultural PolicyDO - 10.24843/UJLC.2018.v02.i01.p01, 2018)
Employment relationship can be ended in many ways and under different circumstances. This article discusses the rules in Finland regarding the termination of employment contract. It analyses in outline what can be considered as a proper and weighty reason or an extremely weighty reason to end an employment contract. The Finnish Employment Contracts Act demands that there must always be a proper and weighty reason to end the employment contract. If the employer wants to end the employment contract summarily without notice, there must even be an extremely weighty reason to do that. Even though the employment legislation stipulates that there must be a legal ground to end the employment contract, the legislation does not contain any list of the acceptable grounds of termination or cancellation of the employment contract. In the legal practice and legal literature, it has been argued that the proper and weighty reason may be for example the neglect of the work obligations, competing activity and violating of the business secrets, use of intoxicants, criminal activity and inappropriate behaviour and in some cases even illness. However, the grounds for the termination or cancellation of the employment contract cannot be precisely defined because every termination and cancellation of the employment contract is unique.